Neural crest origin of olfactory ensheathing glia - Barraud, Perrine (National Academy of Sciences, 2010)
Olfactory ensheathing cells (OECs) are a unique class of glial cells with exceptional translational potential because of their ability to support axon regeneration in the central nervous system. Although OECs are similar in many ways to immature and nonmyelinating Schwann cells, and can myelinate large-diameter axons indistinguishably from myelination by Schwann cells, current dogma holds that OECs arise from the olfactory epithelium. Here, using fate-mapping techniques in chicken embryos and genetic lineage tracing in mice, we show that OECs in fact originate from the neural crest and hence share a common developmental heritage with Schwann cells. This explains the similarities between OECs and Schwann cells and overturns the existing dogma on the developmental origin of OECs. Because neural crest stem cells persist in adult tissue, including skin and hair follicles, our results also raise the possibility that patient-derived neural crest stem cells could in the future provide an abundant and accessible source of autologous OECs for cell transplantation therapy for the injured central nervous system.